Demographic responses to mercury exposure in two closely related Antarctic top predators. Issue 4 (1st April 2014) - Goutte, A.; Bustamante, P.; Barbraud, C.; Delord, K.; Weimerskirch, H.; Chastel, O.
Abstract : Although toxic chemicals constitute a major threat for wildlife, their effects have been mainly assessed at the individual level and under laboratory conditions. Predicting population‐level responses to pollutants in natural conditions is a major and ultimate task in ecological and ecotoxicological research. The present study aims to estimate the effect of mercury (Hg) levels on future apparent survival rates and breeding performances. We used a long‐term data set (∼10 years) and recently developed methodological tools on two closely related Antarctic top predators, the South Polar Skua Catharacta maccormicki from Adélie Land and the Brown Skua C. lonnbergi from the Kerguelen Archipelago. Adult survival rates and breeding probabilities were not affected by Hg levels, but breeding success in the following year decreased with increasing Hg levels. Although South Polar Skuas exhibited much lower Hg levels than Brown Skuas, they suffered from higher Hg‐induced breeding failure. This species difference could be attributed to an interaction between Hg and other environmental perturbations, including climate change and a complex cocktail of pollutants. By including Hg‐dependent demographic parameters in population models, we showed a weak population decline in response to increasing Hg levels. This demographic decline was more pronounced in South Polar Skuas than in Brown Skuas. Hence, Hg exposure differently affects closely related species. The wide range of environmental perturbations in Antarctic regions could exacerbate the demographic responses to Hg levels. In that respect, we urge future population modeling to take into account the coupled effects of climate change and anthropogenic pollution to estimate population projections.